2004
DOI: 10.1016/j.jvs.2004.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrating surgery and radiology in one suite: A multicenter study

Abstract: Integration of digital angiographic systems into operating rooms has produced opportunities for new treatments and offers a superior solution for interdisciplinary work among surgeons, cardiologists, and radiologists. However, the context of use differs radically from that in the traditional radiologic examination room; the environment, users, and procedures are all different. Integration of imaging methods into the operating room can be more successful if special operating room conditions are taken into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Some are located in the cardiac catheterization (232) or interventional suites, while others are upgraded operating rooms (233,234). Ideally, the hybrid suite would be located in a single cardiovascular procedural area, where standard catheterization laboratories are in the same general area as open heart surgical suites, so that the people (cardiologists, surgeons, catheterization technicians, operating room technicians, perfusionists) and equipment (catheters, stents, cardiopulmonary bypass, perfusionist equipment, surgical equipment) are readily available for all conventional catheterization laboratories, operating rooms, or hybrid suites.…”
Section: Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are located in the cardiac catheterization (232) or interventional suites, while others are upgraded operating rooms (233,234). Ideally, the hybrid suite would be located in a single cardiovascular procedural area, where standard catheterization laboratories are in the same general area as open heart surgical suites, so that the people (cardiologists, surgeons, catheterization technicians, operating room technicians, perfusionists) and equipment (catheters, stents, cardiopulmonary bypass, perfusionist equipment, surgical equipment) are readily available for all conventional catheterization laboratories, operating rooms, or hybrid suites.…”
Section: Locationmentioning
confidence: 99%
“…The interventional cardiologist requires a radiolucent table with a full range of motion and a floating tabletop to allow fast movements during angiography. Both requirements are satisfied by a nonmetallic, carbon-fiber surgical table, with floating table-top and lateral and vertical tilt (234). Most tables designed for hybrid suites include in their specifications adequate weight tolerance (e.g., over 450 lb), longitudinal and lateral displacement, height displacement (e.g., 28 to 48 inches [685 to 1180 cm]), lateral tilt (e.g., 20°or more), and Trendelenburg and reverse Trendelenburg tilt (20°or more).…”
Section: Table Requirementsmentioning
confidence: 99%
“…A hybrid OR should be larger than a standard OR, and the basic principle for planning is the larger the better, because it is not only the imaging equipment that needs sufficient space. Staff calculations have shown that in hybrid procedures 8 to 20 people are needed in the team including anesthesiologists, surgeons, nurses, technicians, perfusionists, experts form device companies, and so forth [ten Cate 2004]. Expert opinions recommend for newly built ORs at least 70 m 2 [Benjamin 2008].…”
Section: Room Size and Preparationmentioning
confidence: 99%
“…The design team felt a better solution was to create a "hybrid" OR by including highquality multi-purpose angiography equipment within a trauma OR. This would allow for a wide range of imageguided endovascular and interventional radiology procedures, on-table diagnostics and quality assessments, or formal open surgery as required, expediting patient care (ten Cate et al, 2004).…”
Section: Introductionmentioning
confidence: 99%